An index of events in the military history of the Greek Nation (An Army History Directorate Publication, 1998)
This work is a summary and chronological record of the most important war-military events, along with the political-diplomatic events directly related to them which have been highlighted globally on the nation's long historical course. The main sources of this publication are the historical archives of the Army Department of History, the history of the Greek nation published by Athens House, encyclopedias and various historical editions of other Greek publishers.